2019
DOI: 10.1097/j.pain.0000000000001538
|View full text |Cite
|
Sign up to set email alerts
|

A deeper look at pain variability and its relationship with the placebo response: results from a randomized, double-blind, placebo-controlled clinical trial of naproxen in osteoarthritis of the knee

Abstract: Previous studies have shown a robust correlation between variability of clinical pain scores and responsiveness to placebo (but not active drug) in pain studies, but explanations for these relationships are lacking. We investigated this further by assessing relationship between the Focused Analgesia Selection Test (FAST), a psychophysical method that quantifies pain reporting variability in response to experimental stimuli, variability of daily clinical pain scores as captured using diary, and response to trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 28 publications
0
33
4
Order By: Relevance
“…Furthermore this study has demonstrated that FidHycarn using two safe products: carnosine and HA has a bio-pharmacological effect comparable to the treatment with naproxen (a standard treatment for OA but with proven side effects) [53], at the clinical dose per kg, for almost all the parameters assessed, without significant statistical differences. In conclusion, the results obtained demonstrate for the first time in an animal model of osteoarthritis the effectiveness of oral administration of the conjugate FidHycarn compared to the administration of the individual components.…”
Section: Discussionmentioning
confidence: 73%
“…Furthermore this study has demonstrated that FidHycarn using two safe products: carnosine and HA has a bio-pharmacological effect comparable to the treatment with naproxen (a standard treatment for OA but with proven side effects) [53], at the clinical dose per kg, for almost all the parameters assessed, without significant statistical differences. In conclusion, the results obtained demonstrate for the first time in an animal model of osteoarthritis the effectiveness of oral administration of the conjugate FidHycarn compared to the administration of the individual components.…”
Section: Discussionmentioning
confidence: 73%
“…Patients without sensory precision training had significantly higher placebo responses 134. A subsequent replication study in patients with knee osteoarthritis (n=55) found analogous results 135…”
Section: Evidence For Theories Of Placebo Effectsmentioning
confidence: 77%
“…There are many factors that can contribute to a high placebo response such as the placebo effect itself, natural improvement in the population, poor research or study design, and regression to the mean (1). For neurological disorders such as neuropathic pain and Parkinson’s disease, a high placebo response has indeed been shown to have an impact on the separation between placebo and active treatment (24).…”
Section: Introductionmentioning
confidence: 99%